Legal Protection of Hajj and Umrah Pilgrims Under Indonesia’s Amended Pilgrimage Law: A Doctrinal Analysis - Fani Ruusul Masail (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2026)
Hajj and Umrah services in Indonesia combine religious observance with public administration, cross-border mobility, financial transactions, and commercial service relationships, exposing pilgrims to both regulatory and contractual risks. Law No. 14 of 2025 amended Indonesia’s sector-specific pilgrimage legislation, but the relationship among pilgrims’ statutory rights, governmental responsibility, organizer accountability, and general consumer protection requires systematic clarification. This article examines how the amended framework regulates pilgrims’ rights and protection, allocates responsibilities between the government and pilgrimage organizers, and structures supervision, accountability, and legal remedies. The study employs doctrinal legal research using statutory and conceptual approaches. Its primary legal materials comprise Law No. 8 of 2019 as amended by Law No. 14 of 2025, Law No. 8 of 1999 on Consumer Protection, and relevant implementing regulations. These materials are analyzed through grammatical, systematic, and doctrinal interpretation. The findings demonstrate that Indonesian law does not establish a uniform protection model. Regular Hajj is governed primarily through direct governmental responsibility; special Hajj and licensed Umrah combine statutory protection with regulated contractual duties; and independent Umrah relies more heavily on agreements with individual service providers while excluding pilgrims from several organizer-based protections. Consumer protection law complements, but does not replace, the sector-specific framework by providing general rights to information, compensation, and dispute resolution. The article contributes a differentiated doctrinal model of pilgrim protection and recommends regulatory harmonization, transparent licensing and evaluation information, traceable financial transactions, integrated complaint mechanisms, and consistent enforcement.